Environmentally-Safe Catalytically Active and Biocide Polymer-Metal Nanocomposites with Enhanced Structural Parameters - Alonso, Amanda; Macanás, Jorge; Davies, Gemma-Louise; Gounko, Yuri; Muñoz, Maria; Muraviev, Dmitri (IntechOpen, 2011)
None